Sectoral Analysis of Human Capital Investment, Labor Productivity and Poverty in Nigeria - Osayuwamen Lillian Omorenuwa; Aderopo Raphael Adediyan (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
This paper is on the analysis of human capital investment and labor productivity in a situation of a rising incidence of poverty in Nigeria on a sectoral basis. The analysis was done using annual time series data between 1986 and 2019. Three sectors were considered in the study: the agricultural, industrial and service sectors. The study used the Autoregressive Distributive Lag (ARDL) technique to estimate each of the stated models. Based on the estimated model, central in the results of the study is in two folds. In the first case, there is a direct positive effect of human capital investment on labor productivity, and a direct negative impact of poverty on labor productivityover time across the three sectors. In the second case, poverty decreases the contribution of human capital investment to labor productivity growth in the agricultural and industrial sectors in the short run only. But there is insufficient evidence on this in the service sector.